2021
DOI: 10.3389/fmed.2021.654250
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Diet to Slow CKD Progression

Abstract: Due to the unique role of the kidney in the metabolism of nutrients, patients with chronic kidney disease (CKD) lose the ability to excrete solutes and maintain homeostasis. Nutrient intake modifications and monitoring of nutritional status in this population becomes critical, since it can affect important health outcomes, including progression to kidney failure, quality of life, morbidity, and mortality. Although there are multiple hemodynamic and metabolic factors involved in the progression and prognosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 138 publications
(124 reference statements)
0
21
0
4
Order By: Relevance
“…A prospective cohort study conducted in Japan reported a null association between total protein and all-cause mortality ( 23 ). Most studies, which analyze the effects of LPD on kidney outcomes have proved the beneficial effects of dietary protein restriction in reducing the decline in renal function and the risk of progression to kidney failure in CKD populations ( 6 , 14 , 37 ). However, unfortunately, the results of a few other studies are not consistent, showing no benefits of protein restriction for patients with CKD ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective cohort study conducted in Japan reported a null association between total protein and all-cause mortality ( 23 ). Most studies, which analyze the effects of LPD on kidney outcomes have proved the beneficial effects of dietary protein restriction in reducing the decline in renal function and the risk of progression to kidney failure in CKD populations ( 6 , 14 , 37 ). However, unfortunately, the results of a few other studies are not consistent, showing no benefits of protein restriction for patients with CKD ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although genetic factors play an important role in the incidence and progression of CKD, most cases are attributed to nutritional factors and are largely preventable ( 5 ). Therefore, dietary modifications and maintaining adequate nutrient homeostasis should be a fundamental strategy in treating patients with CKD ( 6 ). For several decades, low protein intake has been recommended for patients with CKD to slow its progression to end-stage kidney disease and delay renal replacement therapy ( 7 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, research indicates that post-KTx proteinuria can be controlled through the diet [40]. A nutritional intervention to control protein intake could contribute to reduce the overload of protein levels in the glomerular capillaries and renal tubules [41][42][43][44][45]. As a result, hyperfiltration and glomerular pressure decrease, reducing the urinary protein excretion rate [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…The model can be used to guide future cancer research to test whether modification or reversal of dysregulated phosphate metabolism through dietary interventions can alter the clinical course of cancer. Restricted-phosphate diets are currently used to modify the progression of chronic kidney disease [89], and similar diets should be tested for use in patients with obesity-related cancers.…”
Section: Summary and Future Directionsmentioning
confidence: 99%